2020
DOI: 10.2147/ott.s236728
|View full text |Cite
|
Sign up to set email alerts
|

<p>Primary Hepatic Neuroendocrine Tumor Mimicking Ruptured Hepatocellular Carcinoma with AFP Elevation: A Case Report and Literature Review</p>

Abstract: Liver cancer is a common malignant disease in China, while the primary hepatic neuroendocrine tumor (PHNET) is extremely rare presented with various manifestations. We herein describe an interesting PHNET case, which was clinically diagnosed as hepatocellular carcinoma (HCC) based on strong clinical evidence and the national guideline, but confirmed to be PHNET by pathology. A42-year-old Chinese male was admitted for persistent upper abdominal pain, and CT scan revealed a huge liver tumor in the left lobe. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…According to the WHO classification system, PHNET can be classified as grade 1 or grade 2; however, PHNET with grade 3 has not yet been reported ( 6 ). In most cases reported, PHNET was classified as grade 1 or grade 2 based on the WHO classification, however, Huang et al reported a PHNET case with a huge liver tumor, and the pathology demonstrated poorly differentiated neuroendocrine carcinoma (NEC) ( 13 ) In this case, the lesions were positive for CK, synaptophysin, CD56, and P53, and negative for chromogranin marker, with a Ki67 index of 20%. The histopathology and immunohistochemistry results for this patient were consistent with a diagnosis of grade 2 NET.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the WHO classification system, PHNET can be classified as grade 1 or grade 2; however, PHNET with grade 3 has not yet been reported ( 6 ). In most cases reported, PHNET was classified as grade 1 or grade 2 based on the WHO classification, however, Huang et al reported a PHNET case with a huge liver tumor, and the pathology demonstrated poorly differentiated neuroendocrine carcinoma (NEC) ( 13 ) In this case, the lesions were positive for CK, synaptophysin, CD56, and P53, and negative for chromogranin marker, with a Ki67 index of 20%. The histopathology and immunohistochemistry results for this patient were consistent with a diagnosis of grade 2 NET.…”
Section: Discussionmentioning
confidence: 97%
“…As reported by Wang et al ( 12 ), all PHNET lesions show arterial phase enhancement and can be confused with other hypervascular liver lesions, and images showing PHNET lesions causing portal thrombosis have been included in several reports ( 12 ). Huang et al reported a patient with huge PHNET in the left lobe, portal vein tumor thrombus and elevated AFP ( 13 ). In this case, after more than 1 year since PHNET was detected, the development of the tumor produced portal venous thrombosis but the AFP value was within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…AFP is the most classical tumor marker, and 400 ng/ mL is often used as the cutoff value in patients with nonruptured HCC. However, different studies have a different selection of the cut-off value of AFP in rHCC [42][43][44][45]. Hence, we chose to use an ROC curve to determine the cutoff value, and we evaluated the relationship between AFP and the OS and RFS in rHCC patients with or without cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 The elevation of AFP was suggested to be related to secretion by immature hepatocytes and induced progenitor cells. 4 Fibroblast activation protein is overexpressed in cancer-associated fibroblasts, and PET tracers acting like inhibitors of this molecule have been used in imaging of different kind of tumors in recent years. [5][6][7] Tumor-to-background contrast ratios are reported to be equal to or even better than those of 18 F-FDG.…”
mentioning
confidence: 99%
“…There are very few reports in the literature showing elevated AFP levels in primary or metastatic neuroendocrine tumors of the liver. [1][2][3][4] AFP-secreting hepatic neuroendocrine carcinomas were usually reported with other malignant components such as hepatocellular carcinoma. 2 In our case, the AFP level was much higher than the previous reports.…”
mentioning
confidence: 99%